Efficacy of telmisartan for the treatment of persistent renal proteinuria in dogs: A double‐masked, randomized clinical trial. (9th November 2020) - Lourenço, Bianca N.; Coleman, Amanda E.; Brown, Scott A.; Schmiedt, Chad W.; Parkanzky, Max C.; Creevy, Kate E.
Abstract: Background: Information regarding efficacy of the angiotensin II receptor blocker, telmisartan, for treatment of proteinuria in dogs is limited. Objective: To evaluate the antiproteinuric efficacy of telmisartan, as compared to enalapril, in dogs with chronic kidney disease and persistent, renal proteinuria. Animals: Thirty‐nine client‐owned dogs with chronic kidney disease and urinary protein‐to‐creatinine ratio (UPC) > 0.5 (if azotemic) or ≥ 1.0 (if nonazotemic). Methods: In this prospective, randomized, double‐masked clinical trial, dogs were block randomized, according to presence or absence of azotemia and systemic arterial hypertension, to receive telmisartan (1.0 mg/kg PO q24h), or enalapril (0.5 mg/kg PO q12h), and followed for 120 days. Up‐titration of study drug dosage on days 30 and 60, and addition of the other study drug at day 90, were performed if UPC > 0.5 was noted at these visits. Percentage change in UPC relative to baseline was calculated for all time points. Data are presented as median (range). Results: Thirty‐nine (20 telmisartan‐treated, 19 enalapril‐treated) dogs were included. At day 30, percentage change in UPC was greater for telmisartan‐treated (−65% [−95% to 104%]) vs enalapril‐treated (−35% [−74% to 87%]) dogs ( P = .002). Among dogs persistently proteinuric at earlier visits, telmisartan remained superior to enalapril at days 60 ( P = .02) and 90 ( P = .02). No difference in percentage change in UPC between study groups was observed at day 120, when combination therapy was allowed. Combination therapy resulted in relevant azotemia in 4/13 (31%) dogs. Conclusions and Clinical Importance: Telmisartan might be a suitable first‐line therapy for dogs with renal proteinuria.